Determination of Phytochemical Constituents and Insecticidal Activity of Eucalyptus Globules against Cactus Pests (Global Journal of Science Frontier Research, 2015)
Cactus pear is widely distributed in Tigray and South Amhara Regional state and is the integral part of the economy of the people. It is commonly used as a famine food, feed for livestock, bee forage, a source of cash income and short time occupation, soil and water conservation, live fences etc. However, cactus is been gradually destroyed. The peoples relied on cactus are suffering from the destruction. The effect of the insect cochineal has been an alarm around the region. The intention of this research was to find a solution to insects and pests on cactus. Insecticidal activity was done on Eucalyptu soil extracts and on three commercial pesticides. At all concentrations the oils terminate the cochineal insects of all ages. Especially, the male cochineals (adult and young) and young female were more sensitive to the oils respectively. Findings from spray test are promising with 80-90% inhibition in average.
Keywords: opnitiaficusindica; eucalyptus globulus; hydro distillation; essential oil; phytochemical screening; physicochemical constants; insecticidal activity